PENGEMBANGAN E-MODUL PEMBELAJARAN TEMATIK BERBANTUAN CANVA UNTUK PESERTA DIDIK KELAS IV - Maratul Qiftiyah (Adi Widya: Jurnal Pendidikan Dasar, 2024)
This research aims to find out how to develop canva assisted thematic learning e-modules, determine the feasibility of Canva assisted thematic learning e-modules, and determine the response of educators and students to the use of canva assisted thematic learning e-modules. This research is a type of research and development using the ADDIE model. Based on the analysis of the needs of educators and students, it was concluded that students need the e-learning modules that researchers have developed. Canva assisted thematic learning e-modules are validated by media experts and material experts. Thematic learning e-modules were tested on 24 class IV students at SDN 1 Sumber Agung. Thematic learning e-modules are produced through stages, namely analysis, design, development, implementation, and evaluation. The results of validation by material experts were carried out twice, obtaining an overall score of 88% with the criteria "very valid". Meanwhile, the results of validation by media experts which were carried out twice obtained a total score of 85% with the requirement "very valid". The results of the trial from the response questionnaire of 24 class IV students obtained a score of 83.5% which was included in the "very practical" criteria, while the assessment results given by educators obtained an average percentage score of 90% with the "very practical" criteria.